Pengaruh Ukuran Perusahaan dan Profitabilitas Terhadap Agresivitas Pajak : Studi Pada Perusahan Sektor Barang Konsumen Primer Subsektor Makanan dan Minuman di Bursa Efek Indonesia - Daho, Maria Clarita Cherlinde; Sudirman, Ganefo (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the effect of firm size and profitability on tax aggressiveness in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. A quantitative approach was employed using multiple linear regression to examine the relationships between variables. Secondary data were obtained from annual reports and financial statements published on the official stock exchange website and the respective company websites. Firm size was proxied by total assets transformed into their natural logarithm, while profitability was measured using the return on assets ratio. Tax aggressiveness was proxied by the effective tax rate. The results indicate that firm size has a significant positive effect, whereas profitability has a significant negative effect on tax aggressiveness. These findings provide implications for corporate management and policymakers to consider internal factors in formulating effective and sustainable tax management strategies.